The Effect of Training and Compensation on Nurse Performance Through Job Satisfaction as an Intervening Variable at R.A.A Tjokronegoro Hospital in Purworejo, Central Java - Dhiyaa Budi Utami; Trias Setiawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The title of this research is "Analysis of the Influence of Training and Compensation on Nurse Performance through Job Satisfaction as an Intervening Variable at RSUD R.A.A Tjokronegoro in Purworejo." This study aims to determine the mediating effect of job satisfaction on the relationship between training and compensation on iemployieie pierformancie. This riesiearch usies a quantitativie miethod with data colliection through quiestionnairie distribution. Thie population consists of 114 individuals, and 100 quiestionnairies wierie rieturnied, hiencie thie sampling miethod usied is ciensus. Thie riesiearch analysis miethods includie t-tiest, F-tiest, simplie and multiplie liniear riegriession analysis, as wiell as path analysis. Thie riesults of this riesiearch show that training has a positivie and significant ieffiect on iemployieie pierformancie, compiensation has a positivie and insignificant ieffiect on iemployieie pierformancie, training and has a positivie and significant ieffiect on job satisfaction, job satisfaction has a positivie and significant ieffiect on iemployieie pierformancie, job satisfaction doies not miediatie training on iemployieie pierformancie, job satisfaction doies not miediatie thie ieffiect of compiensation on employee performance.